ETHANOL SEPARATION USING SEPABEADS207 ADSORBENT (Jurnal Teknologi (Sciences & Engineering), 2017)
This work was aimed at evaluating the ethanol separation using Sepabeads207 adsorbent. A 10 wt% of ethanol solution was used as a model fermentation broth. The separation of ethanol from the solution was performed in a tube containing Sepabeads207 at different operating conditions: temperatures, 20 to 40oC; solution pH, 4 to 7; and contact times, 5 to 25 minutes. Recovery of ethanol via stripping was studied between 15 and 35 minutes, and at different air temperatures of 80 to 95oC. The concentration of liquid ethanol was measured using gas chromatography and refractometer. A higher ethanol concentration by Sepabeads207 adsorption was obtained at 20oC and solution pH 4 for 5 minutes, while the recovery was performed better at 80oC for 15 minutes. By applying these conditions, 10 wt% of ethanol in the solution was concentrated to 46 wt%. The ethanol adsorption data are: i). capacity of 0.22 g ethanol/g adsorbent, ii). selectivity of 7.75 (g ethanol/g water (adsorbed)) / (g ethanol/g water (original solution)), and iii). efficiency of 100%. Sepabeads207 is a promising adsorbent for ethanol separation from the dilute ethanol solution.